2021
DOI: 10.1021/acs.jpca.0c11136
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis Production and Spectroscopic Investigation of the Highest Vibrational States in H2 (X1Σg+ v = 13, 14)

Abstract: Rovibrational quantum states in the X 1 Σ g + electronic ground state of H 2 are prepared in the v = 13 vibrational level up to its highest bound rotational level J = 7, and in the highest bound vibrational level v = 14 (for J = 1) by two-photon photolysis of H 2 S. These states are laser-excited in a subsequent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…The H 2 products arising via the former route carry substantial vibrational but little rotational excitation. Previous REMPI studies have reported formation of H 2 products in high v ′′, low J ′′ states following excitation of H 2 S to similar total energies 46 50 . The P ( E T ) distributions measured when exciting parent levels with < J b 2 >> 0 reveal a rival Coriolis-induced pathway yielding additional H 2 products, characterised by little vibrational but massive rotational excitation—including population of super-rotor levels of H 2 .…”
Section: Resultsmentioning
confidence: 93%
“…The H 2 products arising via the former route carry substantial vibrational but little rotational excitation. Previous REMPI studies have reported formation of H 2 products in high v ′′, low J ′′ states following excitation of H 2 S to similar total energies 46 50 . The P ( E T ) distributions measured when exciting parent levels with < J b 2 >> 0 reveal a rival Coriolis-induced pathway yielding additional H 2 products, characterised by little vibrational but massive rotational excitation—including population of super-rotor levels of H 2 .…”
Section: Resultsmentioning
confidence: 93%
“…They assigned transitions between highvibrational states in H 2 to both inner and outer well states in the EF 1 Σ + g double well potential. However, in the controlled two and three-laser studies probing X(v = 11 − 14) [41][42][43][44] only transitions to the F 1 Σ + g outer well could be confirmed. In an alternative study, starting from the photolysis of H 2 CO, therewith producing H 2 vibrational states of intermediate quantum numbers X(v = 3 − 9), two-photon transitions to both EF 1 Σ + g inner and outer well were found [45].…”
Section: Introductionmentioning
confidence: 91%
“…The photolysis resonance at 291 nm was used for the production and investigation of H 2 molecules in v = 11 vibrational states [43]. For the production of H 2 in v = 13, 14 levels photolysis on the two-photon resonance at 281.8 nm was employed [44]. In the present experiment the wavelength of the dissociation laser is tuned to this two-photon absorption resonance in H 2 S at 281.8 nm, providing sufficient energy to overcome the dissociation energy, at 69935(25) cm −1 , for a complete three particle dissociation [53,54] with an excess of 1000 cm −1 above threshold.…”
Section: S H Hmentioning
confidence: 99%
See 2 more Smart Citations